IMPROVING THE ACCOUNTING OF GOODS AND MATERIAL RESOURCES BASED ON INTERNATIONAL STANDARDS - Bekimmatovich, Palvanov Husnidin (Research Parks Publishers, 2023)
This article describes the improvement of inventory accounting based on international standards. As a result of the conducted research, proposals for improving inventory accounting based on the requirements of international standards are presented.